2021
DOI: 10.1016/j.ejvs.2020.08.034
|View full text |Cite|
|
Sign up to set email alerts
|

Five Year Patient Outcomes of Endovascular Abdominal Aortic Aneurysm Repair in the ENDURANT France Registry

Abstract: WHAT THIS PAPER ADDSThis analysis of the ENDURANT France registry provides five year outcomes from a French population treated under real life conditions. Patients experienced a 69.9% AE 3.5% KaplaneMeier overall survival, 97.6% AE 1.2% freedom from aneurysm related mortality, low rates of type IA endoleaks, few secondary procedures, and showed positive signs of remodelling. These outcomes are similar to other recent global registries and better than the outcomes with earlier generation devices. With the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…18,19 Our study showed significantly increased mortality in the EVAR group 5 years after the procedure, compared with OSR, and the 5-year overall survival of EVAR patients was somewhat lower than the data reported by others. 13,18,19 Although the EVAR procedure is an independent risk factor for 5-year mortality, we cannot ignore the imbalance in the baseline characteristics between the EVAR and OSR groups. Significantly higher mean age and greater proportion of renal and cerebrovascular comorbidities among EVAR patients may influence not only the choice of treatment modality, but also prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Our study showed significantly increased mortality in the EVAR group 5 years after the procedure, compared with OSR, and the 5-year overall survival of EVAR patients was somewhat lower than the data reported by others. 13,18,19 Although the EVAR procedure is an independent risk factor for 5-year mortality, we cannot ignore the imbalance in the baseline characteristics between the EVAR and OSR groups. Significantly higher mean age and greater proportion of renal and cerebrovascular comorbidities among EVAR patients may influence not only the choice of treatment modality, but also prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, improvements in the design and delivery of modern stent grafts have reduced the frequency of those adverse events over 5 years and beyond. 12,13 Although EVAR has been widely adopted and the initial results have been promising, comparison of its long-term efficacy against OSR still remains elusive, and late-onset aortic complications need to be systematically evaluated. Usage of older-generation stent grafts on the on hand, and the relatively small number of patients in controlled trials with longterm results on the other hand, are the limitations to comparison of long-term survival after elective OSR and EVAR.…”
Section: Five-year Survival After Elective Open and Endovascular Aortic Aneurysm Repairmentioning
confidence: 99%
“…In this issue, Becquemin et al 1 demonstrate promising long term results using the Endurant stent graft in a multicentre French single arm post-market registry, with a KaplaneMeier five year freedom from type IA endoleaks and secondary endovascular procedures of 94.5 AE 1.7% and 90.4 AE 2.6%, respectively. Proponents of endovascular aortic repair (EVAR) may use this study as another example that EVAR has almost reached a state of perfection.…”
mentioning
confidence: 99%